THE VALUES OF A CULTURE THROUGH TIME - Omarova Aklima; Gafurbekov Tuktasyn; Matyzhanov Kenzhehan; Kaztuganova Ainur; Bakyt Turmagambetova (Scientific Journal of Pedagogy and Economics, 2021)
The article is aimed at actualizing the intrinsic value of M.O. Auezov’s creative heritage in the context of real processes of modernization of public consciousness. It presents methodological and theoretical guidelines for the research which is fundamentally new in terms of its approaches, in which the factor of the existing and future impact of M.O. Auezov – the subject and creator of culture – on society should be revealed in the coordinates of the transnational space in all its convincing power and unconditional character. The choice of this particular format is due to the combination of objective and subjective reasons, relying on the achievements in the field of humanitarian knowledge and focusing on the historical and theoretical issues of modern art history, that made it possible to generalize the accumulated material and determine the conceptual foundations and strategy in ensuring the level of scientific reliability, novelty characteristic of fundamental developments and significance of the tasks to be solved and the expected results. The dynamics and effectiveness of direct and indirect participation in the process of intercultural interaction and determination of universal values can be shown based on the analysis of the selected samples of research, artistic, educational, organizational activities of M.O. Auezov, the coverage of all forms of influence on the development of art in its species diversity, understanding the re-interpretive practice of different years (with an emphasis on socially significant results), including art history interpretation of the works of different genres, created according to the texts of M.O. Auezov or dedicated to his memory. The attraction of new archival data, experience of foreign reception, reconstruction of "forgotten" facts will deepen the understanding of the true scale of personal impact on the development of culture in the XX-XXI centuries. Awareness of the phenomenal productivity of M.O. Auezov in asserting the uniqueness of the heritage and traditions of the Kazakh people is significant both for a worthy presentation of Kazakhstan at the world level, and for expanding the "horizons" of enriching the spiritual potential of the nation.